Penyuluhan Tentang Kesehatan Paru di Universitas Adiwangsa Jambi - Melly Miranda; Thabina Anindya Rizaldi; Subang Aini Nasution; Meki Karolina (Universitas Adiwangsa Jambi, 2026)
Lung health is an important aspect of maintaining quality of life and human productivity. The high incidence of lung diseases influenced by risk factors such as smoking, air pollution, and limited public knowledge highlights the importance of health education as a promotive and preventive effort. This activity aimed to improve students’ knowledge and awareness regarding lung health and lung disease prevention. The method used was health education through lectures and interactive discussions involving 40 students from the Faculty of Medicine, Universitas Adiwangsa Jambi. Evaluation was conducted using pre-tests and post-tests consisting of 15 multiple-choice questions. The results demonstrated an improvement in participants’ knowledge after the educational intervention. Before the activity, 2 participants had low knowledge, 28 had moderate knowledge, and 10 had high knowledge levels. After the intervention, no participants remained in the low-knowledge category, 7 participants were in the moderate category, and 33 participants achieved high knowledge levels. These findings indicate that lung health education was effective in improving participants’ knowledge and awareness regarding the importance of maintaining lung health and preventing lung diseases. Health education can serve as a promotive and preventive strategy to support the improvement of public health.